2020
DOI: 10.1186/s12877-020-01733-2
|View full text |Cite|
|
Sign up to set email alerts
|

Factors associated with self-rated health in a Norwegian population of older people participating in a preventive home visit program: a cross-sectional study

Abstract: Background Assessing self-rated health by preventive home visits of older people can provide information about the person’s well-being, quality of life and risk of developing illness. The aim of this study was to examine associations between self-rated health and factors related to demographics, lifestyle, health conditions and medical diagnoses by older people participating in a preventive home visit program. Methods A cross-sectional study including 233 participants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“… 11 Recent studies have demonstrated the association between Internet usage and better self-rated health in older adults. 12 , 13 , 14 , 15 Further, Fjell et al 14 suggested that Internet usage can enhance older adults’ self-rated health by improving social support, social contact, and access to health information. However, some studies reported no significant association between Internet usage and self-rated health 16 or negative associations.…”
Section: Introductionmentioning
confidence: 99%
“… 11 Recent studies have demonstrated the association between Internet usage and better self-rated health in older adults. 12 , 13 , 14 , 15 Further, Fjell et al 14 suggested that Internet usage can enhance older adults’ self-rated health by improving social support, social contact, and access to health information. However, some studies reported no significant association between Internet usage and self-rated health 16 or negative associations.…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, this is the first study on self-rated health in the south-western health zone of Malawi. Although the prevalence of poor SRH is lower than those of other Sub-Saharan African (SSA) countries with higher per capita expenditure on health, and comparable to findings from high-income settings it ought to be considered as suboptimal and a cause for concern [ 12 14 , 22 , 23 , 27 ]. The latter is due to Malawi’s good SRH prevalence that is below the continental mean [ 21 ] .…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, this is the rst study on self-rated health in the south-western health zone of Malawi. Although the prevalence of poor SRH is lower than some gures from Sub-Saharan Africa (SSA) and comparable to ndings from high-income settings it ought to be considered as suboptimal and a cause for concern (12,14,(24)(25)(26). The latter is due to Malawi's resource constraints, growing double burden of communicable and non-communicable diseases, increasing life expectancy, and declining mortality from conditions that once carried high mortality (27,28).…”
Section: Prevalence Of Poor Srhmentioning
confidence: 99%